2000
DOI: 10.1007/pl00011701
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between interleukin-1-alpha concentration in tumors and cell growth in gastric cancer, determined using flow cytometry

Abstract: BACKGROUND: Interleukin-1-alpha (IL-1alpha) produced by tumor cells stimulates the proliferation or the growth of several cancer cell lines. The aim of this study was to clarify the relationship between growth activity evaluated by DNA analysis and the concentration of tumor-derived IL-1alpha in gastric cancers in clinical cases.METHODS: We measured the concentration of IL-1alpha in homogenized tumor samples obtained from 49 patients with gastric cancer, using an enzyme-linked immunosorbent assay, and we analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For example, systemic inflammation by injection of IL-1␣ is shown to enhance the metastasis of melanoma into the liver (52). A higher level of IL-1␣ was observed in colorectal cancer from patients with liver metastasis than in those without liver metastasis (53,54). We speculate that the paradigm shown by the current study for IL-1-mediated MMP-9 induction and activation by HSC may also contribute to metastasis of tumors including hepatocellular carcinomas.…”
Section: Inactivation Of Mmp-9 By Timp-1 or Depletion Of Mmp-9 By Gelmentioning
confidence: 51%
“…For example, systemic inflammation by injection of IL-1␣ is shown to enhance the metastasis of melanoma into the liver (52). A higher level of IL-1␣ was observed in colorectal cancer from patients with liver metastasis than in those without liver metastasis (53,54). We speculate that the paradigm shown by the current study for IL-1-mediated MMP-9 induction and activation by HSC may also contribute to metastasis of tumors including hepatocellular carcinomas.…”
Section: Inactivation Of Mmp-9 By Timp-1 or Depletion Of Mmp-9 By Gelmentioning
confidence: 51%
“…Selection of polymorphisms in this study was based on biologic properties of the genes and previously published literature. IL-1s are a cluster of genes whose products have an important role in controlling inflammatory reactions, as well as controlling the acidity of the stomach [7,8,28]. To our knowledge, only one previous study has examined the association between IL-1A À889 polymorphisms and GC and found no association [17].…”
Section: Discussionmentioning
confidence: 70%
“…We previously evaluated the liver-metastatic ability of several gastric can- cer cell lines via intrasplenic liver metastasis assay and classified them as high liver-metastatic (MKN74) or low liver-metastatic (MKN45 and NUGC-4) [29]. Recent research has demonstrated that IL-1␣ contributes to the regulation of tumor growth, progression, and liver metastasis in primary gastric carcinoma [12,30,31]. In the present study, we demonstrated that IL-1␣ mRNA and protein were detected only in the high liver-metastatic gastric cancer cell line MKN74, but not in the low liver-metastatic cell lines MKN45 or NUGC-4.…”
Section: Discussionmentioning
confidence: 99%